APPLICATION OF CAD/CAM SYSTEMS IN THE MANUFACTURING OF ORTHOPEDIC DENTAL STRUCTURES - Osmanova Safiya; Guseynova Sabina Tagirovna; Akhmedov Alisher Astanovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Imagine that in one step you make an impression, simulate a restoration and install a crown for the patient. Fiction? No, this is the same CAD/CAM system — Computer Assisted Design/Computer Aided Manufacturing or a system for computer modeling and manufacturing dentures. CAD/CAM technologies and system components In CAD/CAM, CAD technologies are computer programs that are involved in creating a 3D model of a tooth or dental system. CAM is a software program that works on creating a physical object — a crown of the same tooth and restoration of the dental system. According to CAD/CAM technology, prosthetics are performed in four stages. • Scanning of the oral cavity to create a virtual 3D model. At this stage, the main component of the system is an intraoral scanner. It reads the geometry of the prosthetic section of the dentition and converts it into a digital model.